2011
DOI: 10.1016/j.jmb.2011.03.065
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Dimeric Autoinhibited Conformation of DAPK2, a Pro-Apoptotic Protein Kinase

Abstract: The death-associated protein kinase (DAPK) family has been characterized as a group of pro-apoptotic serine/threonine kinases that share specific structural features in their catalytic kinase domain. Two of the DAPK family members, DAPK1 and DAPK2, are calmodulin-dependent protein kinases that are regulated by oligomerization, calmodulin binding, and autophosphorylation. In this study, we have determined the crystal and solution structures of murine DAPK2 in the presence of the autoinhibitory domain, with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 58 publications
(75 reference statements)
4
32
0
Order By: Relevance
“…The alg-2 gene was discovered to be a pro-apoptotic calcium binding protein, and it has been proposed that it is involved in calcium mediated signaling processes to regulate cell death. 45,46 In the present research, alg-2 and dapk2 were over-expressed by PFOS. 45 In the present study, alg-2, dapk2 and [Ca 2+ ] i changed concurrently in a similar pattern, demonstrating again that PFOS-induced apoptosis is possibly related to the disturb- ance in calcium homeostasis.…”
Section: Apoptosis Related Gene Expression In the Hippocampussupporting
confidence: 50%
“…The alg-2 gene was discovered to be a pro-apoptotic calcium binding protein, and it has been proposed that it is involved in calcium mediated signaling processes to regulate cell death. 45,46 In the present research, alg-2 and dapk2 were over-expressed by PFOS. 45 In the present study, alg-2, dapk2 and [Ca 2+ ] i changed concurrently in a similar pattern, demonstrating again that PFOS-induced apoptosis is possibly related to the disturb- ance in calcium homeostasis.…”
Section: Apoptosis Related Gene Expression In the Hippocampussupporting
confidence: 50%
“…At the N-terminus, ranging from residue 23 to 285, the enzyme contains its catalytic domain with 80% homology to DAPK1 kinase domain (Kawai et al, 1999). The crystal structure of the kinase domain was resolved a few years ago, suggesting that DAPK2 catalytic domains form dimers (Patel et al, 2011). This is in agreement with the identification of a key structural feature of the DAPK family of proteins, a short segment of mostly positively charged residues termed the basic loop (amino acids 55-66), which was shown to mediate DAPK homodimerization (Zimmermann et al, 2010).…”
Section: Dapk2 Structure and Cell Biological Workhorsesmentioning
confidence: 99%
“…The nature and impact of homodimerization on DAPK2 activity is a matter of controversy. On the one hand, the resolution of the crystal structure of DAPK2 catalytic domain revealed that homodimerization of DAPK2 mediated by binding of two apposed catalytic domains to each other does not allow for substrate binding (Patel et al, 2011), implying decreased DAPK2 activity upon homodimerzation. On the other hand, C-tail deletion mutants demonstrated that homodimerization mediated by the C-terminus increases DAPK2 activity and is necessary for the DAPK2-mediated membrane blebbing (Inbal et al, 2000(Inbal et al, , 2002Shani et al, 2001).…”
Section: Regulation Of Dapk2 Activitymentioning
confidence: 99%
“…modes 1-11 (Majava and Kursula 2009), 1-16 (Osawa et al 1999), and 1-17 (Maximciuc et al 2006) have been identified in crystal structures. Furthermore, the complexes of CaM with peptides from DAP kinases have a combined 1-10-14 mode, where two hydrophobic residues from the peptide lie in the same pocket of CaM in the crystal structures (Kuczera and Kursula 2012; Patel et al 2011). Also, the complex with a myristoylated peptide from CAP-23/NAP-22 has a classical collapsed conformation, even though the ligand peptide does not form an α helix and the myristoyl tail also binds between the CaM lobes (Matsubara et al 2004).…”
Section: Classical Collapsed Cam-peptide Complexesmentioning
confidence: 99%